A Review of Applied Opuntia Forage Production Technologies and Costs for Northeastern Brazil - Suassuna, Paulo (Journal of the Professional Association for Cactus Development, 2008)
The increasing desertification phenomenon in the Brazilian northeastern area is one of the main reasons that lead farmers in this semiarid region to lose their crops. In a partnership survey with EMBRAPA during the 1990s, it was established that the Brazilian northeastern region has an approximate area of 1,600,000 km² and 75% of it (1,200,000 km²) is classified as semiarid. Also, it was acknowledged that in this dry region, 90% of the rural properties are less than 100 ha, and within it, 75% are less than 20 ha. Therefore, the greatest amounts of existing properties in this area are small agricultural modules or properties. The average precipitation in the Brazilian semiarid region ranges from 350 to 800 mm. In this region, there are only two well-defined weather conditions or seasons: rainy (3 to 4 months) and dry (8 to 9 months). It is rather common and cyclical that, from every 7 to 10 years the rainy season just disappears, turning that particular year into a completely dry one: Drought.